2018
DOI: 10.1007/s12350-017-0832-0
|View full text |Cite
|
Sign up to set email alerts
|

Triage of patients for attenuation-corrected stress-first Tc-99m SPECT MPI using a simplified clinical pre-test scoring model

Abstract: While the previously described prediction score effectively identifies patients who can successfully undergo stress-first MPI, it is cumbersome. Triaging based solely on CAD status and with the addition of other key variables is practical and provides improved predictive accuracy for successful stress-first MPI. Utilizing this simplified pre-test scoring model may allow for wider adoption of stress-first imaging protocols which have clear advantages over traditional rest-stress protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…176,177 Despite lack of consensus, one large study enrolling more than 16,000 patients implied that a stress-first study is appropriate in most patients except for those who have known prior myocardial infarction or in those where a two-day protocol is not practical. 37 In this study by Chang et al, 89% of patients had either a history of CAD (31%) or at least an intermediate risk for CAD (58%).…”
Section: Patient Selection For a Stress-first / Stressonly Imaging Prmentioning
confidence: 99%
“…176,177 Despite lack of consensus, one large study enrolling more than 16,000 patients implied that a stress-first study is appropriate in most patients except for those who have known prior myocardial infarction or in those where a two-day protocol is not practical. 37 In this study by Chang et al, 89% of patients had either a history of CAD (31%) or at least an intermediate risk for CAD (58%).…”
Section: Patient Selection For a Stress-first / Stressonly Imaging Prmentioning
confidence: 99%
“…Furthermore, those authors reported that documented CAD was predictive of an abnormal stress MPIin our subjects, only prior MI was independently significant. Gowdar et al [22] revisited the scoring system of Duvall et al and suggested that documented CAD alone was sufficient to triage patients albeit with a slightly lower AUC (0.75). Recently, Rouhani et al [23] have also proposed a clinical scoring system to help identify patients who should undergo stress-only imaging.…”
Section: Discussionmentioning
confidence: 99%
“…In all of these studies, what constitutes a 'normal' stress MPI study is generally understood to be one that can be interpreted confidently without requiring an accompanying rest study for comparison; however, operational definitions have varied in the published literature. Some studies have interpreted normal MPI to mean non-AC SSS ≤ 1 or AC SSS = 0 without restrictions on EF [4], SSS < 3 with EF ≥ 45% [24], and SSS < 3 with EF ≥ 50% [25], Gowdar et al [22] considered values as high as SSS ≤ 3, while Rouhani et al [23] defined it as 'the absence of perfusion abnormalities or other potential ischemic markers (transient ischemic dilatation, right ventricular uptake, etc. ), and the presence of normal left ventricular wall motion and left ventricular ejection fraction'.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the availability of published scoring systems for appropriate patient selection for stress-first/stress-only protocols, there is lack of consensus in this regard. 3,4 Most experts would agree that stress-only imaging should not be performed in those with known or highlikelihood of CAD, prior abnormal scans, or heart failure/reduced left ventricular systolic function. A BMI of greater than 35 kg/m 2 may be considered another criterion for avoiding stress-only imaging, though one study observed that only 22% of patients undergoing bariatric surgery (mean BMI 49 kg/m 2 ) required additional rest imaging.…”
mentioning
confidence: 99%